Associations Between Child Maltreatment, Autonomic Regulation, and Adverse Cardiovascular Outcome in an Urban Population: The HELIUS Study - Bakema, Maryse J.; van Zuiden, Mirjam; Collard, Didier; Zantvoord, Jasper B.; de Rooij, Susanne R.; Elsenburg, Leonie K.; Snijder, Marieke B.; Stronks, Karien; van den Born, Bert-Jan H.; Lok, Anja (Frontiers in Psychiatry, 2020)
Introduction. A mounting body of literature emphasizes the potential negative effects of adverse childhood experiences (ACEs) on both mental and physical health throughout life, including an increased risk for developing cardiovascular disease (CVD). Since CVD is one of the leading causes of mortality and morbidity worldwide, understanding the effects of ACEs on CVD development and identifying the underlying pathways mediating this association is of great importance. Exposure to ACEs may lead to an imbalance in the autonomic nervous system, resulting in a chronically heightened sympathetic activity and lowered reactivity. In a large urban, multi-ethnic population-based cohort study we investigated whether there is an association between ACEs and CVD and if so, whether this relationship is mediated by autonomic dysregulation. Methods. Within the HELIUS study, a large, multi-ethnic population cohort study including n=22,165 Amsterdam residents, we used logistic regression analyses to investigate the association between the number of self-reported ACEs (range 0-4), and self-reported adverse cardiovascular outcome (aCVO). Self-reported ACEs included emotional neglect, emotional abuse, physical abuse and sexual abuse. Furthermore, in a subsample (n=10260), mean age 44.3, we investigated the potential mediation effect of autonomic dysregulation using linear regression analyses. Both baroreflex sensitivity (BRS) and heart rate variability (HRV) were assessed as non-invasive indices of autonomic regulation. Results. The number of endorsed ACE types was significantly associated with a higher aCVO risk. The association remained significant after adjustment for demographic, socio-economic, health-behavioral and psychological covariates (p=0.011, OR: 1.078, CI 1.018, 1.142),) The cumulative exposure to ACEs was negatively associated with BRS and HRV, but the association was no longer significant after correction for socio-economic and demographic covariates and formal mediation analyses were therefore not performed Conclusion. In a large, multi-ethnic urban-population cohort study we observed a positive association between number of endorsed ACEs and self-reported adverse cardiovascular outcome, over and above the effect of relevant demographic, health and psychological factors. However, this association was not mediated by autonomic dysfunction. Future studies should examine the potential role of the dynamics of autonomic dysregulation and other potentially mediating biological pathways